2003
DOI: 10.1080/0269905021000013183
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and affective sequelae in complicated and uncomplicated mild traumatic brain injury

Abstract: This study examined cognitive and affective disturbances in patients with complicated (presence of space occupying lesion) vs uncomplicated (absence of space occupying lesion) mild traumatic brain injury (TBI). It was predicted that the complicated group would perform worse in both domains compared to the uncomplicated group. Participants were 28 patients admitted to an inpatient neurorehabilitation unit with mild TBI and assessed within 40 days of their injury. The complicated group (n = 14) was matched to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(64 citation statements)
references
References 16 publications
3
60
0
1
Order By: Relevance
“…Traumatic abnormalities on CT scan, although typically revealing hemorrhage, may be related to the severity of underlying brain injury. Several authors have found that mTBI patients with cerebral contusions on head CT scan have worse cognitive and neurobehavioral outcomes than mTBI patients with normal CT scans (Borgaro et al, 2003;Iverson, 2006;Kashluba et al, 2008;Levin et al, 2008;Williams et al, 1990). Abnormal CT scan was defined as revealing any of the following traumatic abnormalities: acute hemorrhage (subarachnoid, subdural, epidural, or contusion), edema, or skull fracture.…”
Section: Selection Of Covariates For Multivariate Analysismentioning
confidence: 99%
“…Traumatic abnormalities on CT scan, although typically revealing hemorrhage, may be related to the severity of underlying brain injury. Several authors have found that mTBI patients with cerebral contusions on head CT scan have worse cognitive and neurobehavioral outcomes than mTBI patients with normal CT scans (Borgaro et al, 2003;Iverson, 2006;Kashluba et al, 2008;Levin et al, 2008;Williams et al, 1990). Abnormal CT scan was defined as revealing any of the following traumatic abnormalities: acute hemorrhage (subarachnoid, subdural, epidural, or contusion), edema, or skull fracture.…”
Section: Selection Of Covariates For Multivariate Analysismentioning
confidence: 99%
“…For example, individuals whose Glasgow Coma Scale (GCS) scores are in the generally accepted 'mild' range (i.e., 13-15) and who also demonstrate abnormalities on conventional neuroimaging are described using the term 'complicated mTBI' and their recoveries are more similar to those with GCS-defined moderate, rather than uncomplicated mild, TBI (Borgaro et al, 2003;Iverson, 2006a;Kashluba et al, 2008;Kennedy et al, 2006;Lange et al, 2009;van der Naalt et al, 1999;Williams et al, 1990). Individual difference in neurogenetics relevant to neural repair, neural plasticity, and neurotransmitter function also may influence outcome after mTBI (Arciniegas et al, 2003;Jordan, 2007;McAllister, 2009).…”
Section: Persistent Postconcussive Symptomsmentioning
confidence: 99%
“…Among the mild TBI participants, about 45% of them experienced motor vehicle accidents, 20% of them suffered from falls, 16% of them suffered from assaults, 13% of them suffered from sports-related injuries, and 6% of them had other work related injury. This group of patients were therefore of complicated mild TBI [26,27],showing skull fractures, intracranial haematoma or contusion, or traumatic subarachnoid haemorrhage. Patients were excluded if they were aged below 18; had a head injury that had occurred more than 24 hours previously; had a penetrating skull injury or depressed skull fracture; had an acute focal neurological deficit (motor or cranial nerve) that could not be ascribed to an extracerebral cause (e.g., traumatic mydriasis or peripheral neuropathy); had a seizure before assessment in the Accident and Emergency Department; had a bleeding disorder or were currently using oral anti-coagulants; had returned for reassessment of a pre-existing head injury; were pregnant; had consumed alcohol or used drugs within the last 24 hours; or had a historically established, or history of, chronic alcoholism.…”
Section: Participantsmentioning
confidence: 99%